2007
DOI: 10.1007/s10101-006-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

The use (and abuse) of governance indicators in economics: a review

Abstract: Governance, Institutional quality, Economic growth, O17, O47, P14,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(95 citation statements)
references
References 123 publications
0
80
0
11
Order By: Relevance
“…Critics point to four weaknesses of the ICRG index as a measure of corruption (Williams and Siddique 2008). First, the ICRG index strictly measures the risk to political stability owing to corruption-not corruption itself.…”
Section: The Icrg Indexmentioning
confidence: 99%
“…Critics point to four weaknesses of the ICRG index as a measure of corruption (Williams and Siddique 2008). First, the ICRG index strictly measures the risk to political stability owing to corruption-not corruption itself.…”
Section: The Icrg Indexmentioning
confidence: 99%
“…In contrast to the investor protection indicator, contract-intensive money is more accurately described as realized property rights, as it measures the behavior of individuals in reaction to perceived changes in property rights. Of course, as with all objective indicators, its drawback is that it may capture more than just property rights (see Williams and Siddique 2008 for a critique of its use); however, when paired with the ICRG indicator of investor protection, I believe it will deliver a full picture of both ex ante and ex post property rights.…”
Section: The Data and Empirical Modelmentioning
confidence: 99%
“…In the first instance, as we are attempting to ascertain the profitability of particular banks, as influenced by institutions, contract-intensive money is a suitable proxy as no one bank influences the indicator; that is, while it functions as a vote of confidence in the entire banking sector and property rights in general, unless you are a country like Turkmenistan with a monobank structure, no single bank can dominate the outcome of the indicator. Moreover, while contract-intensive money may sometimes be thought of as a proxy for financial depth (Williams and Siddique 2008), previous empirical tests by Clague et al (1996) have shown that contract-intensive money does indeed capture different effects than broader financial sector development. This is indeed the case here for, as Table 4 shows, while there is some moderate correlation between CIM and other financial depth variables (with the strongest being with country-wide bank capital to assets ratio at 0.5094), the extent of the correlations do not suggest that contract-intensive money cannot be used.…”
Section: The Data and Empirical Modelmentioning
confidence: 99%
“…In fact, this point has been raised by Andrew Williams and Abu Siddique (2008), who note that it might be better thought of as a measure of financial sector development more broadly. However, as I have noted elsewhere (Hartwell 2014a), while this criticism might be true in terms of broader, multi-year movements in contract-intensive money (or for only a point in time, as in cross-sectional data), at a relatively high frequency such as this monthly dataset, contract-intensive money is more likely to capture perceptions of property rights than slowermoving financial sector developments.…”
Section: Empirical Strategy Empirical Modelmentioning
confidence: 99%